The Role of the Effectiveness of Social Media Utilization by the Pangkalpinang City Tourism Office as an Information Medium on Tourist Visit Interest - Sarwindah Sarwindah; Marini Marini; Hengki Hengki; Indah Padilah (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study aims to analyze the role of social media effectiveness used by the Pangkalpinang City Tourism Office as an information medium in increasing tourist visit interest. The background of this research is based on the growing importance of social media as an interactive, informative, and wide-reaching communication and tourism promotion tool. The research method employed is a quantitative approach, with data collected through questionnaires distributed to tourists and social media users who follow the official accounts of the Pangkalpinang City Tourism Office. The findings indicate that the effectiveness of social media usage has a positive and significant influence on increasing tourist visit interest. The regression coefficient value shows that an improvement in social media effectiveness contributes to an increase in visit interest by 0.524. Furthermore, the Adjusted R-Square test result reveals that the effectiveness of social media explains 64.3% of the variation in tourist visit interest, while the remaining 35.7% is influenced by other factors outside the research model. Therefore, it can be concluded that the more effectively social media is utilized as an information and promotional medium, the higher the level of tourist interest in visiting tourism destinations in Pangkalpinang City.